Bahaya Merokok terhadap Kesehatan Reproduksi - Arianggara, Andi Wilda; Roza, Nelli; Handayani, Trisna Yuni; Margiyanti, Norma Jeepi; Sari, Desi Pramita; Tarigan, Renny Adelia; Wilujeng, Ayu Rosanti (JUBDIMAS ( Jurnal Pengabdian Masyarakat), 2024)
Adolescents who smoke are considered a natural behavior in society, the rate of spread of smokers in adolescence reaches high numbers, namely in the age group of 10-14 years and 15-19 years and the age of first-time smokers is in the age group of 15-19 years. In Batam City in 2020, the number of teenagers smoking boys aged 15-19 years is 407 teenagers. and 42 women. The urgency of smoking behavior in adolescents is seen based on the impact of the habit, especially on the long-term effects on adolescent reproductive health. The purpose of this activity is to provide an in-depth understanding of the impact of smoking on the reproductive system, raise awareness about the risks of smoking on reproductive health, and encourage adolescents to maintain reproductive health by avoiding smoking. The methods used in this community service activity are lectures and discussions. The result of this activity is an increase in adolescent knowledge about the risks of smoking on reproductive health. Thus, it is concluded that through education can increase adolescent knowledge about the risks of smoking on their reproductive health.